MicroRNA‐200a suppresses prostate cancer progression through BRD4/AR signaling pathway. (19th February 2019) - Guan, Han; You, Zonghao; Wang, Can; Fang, Fang; Peng, Rui; Mao, Likai; Xu, Bin; Chen, Ming
Abstract: Prostate cancer is still considered a significant health care challenge worldwide due in part to the distinct transformation of androgen‐dependent prostate cancer (ADPC) into treatment‐refractory castration‐resistant prostate cancer (CRPC). Consequently, there is an urgent need to explore novel molecular mechanisms underlying treatment resistance in ADPC. Although numerous studies have alluded to the role of miR‐200a in several cancers, the biological significance of miR‐200a in prostate cancer remains unknown. After performing microarray analysis and reanalysis of the publicly available Memorial Sloan Kettering Cancer Center dataset, miR‐200a expression was found higher in ADPC tissues and its expression was positively associated with survival of CRPC patients. In vitro studies showed that miR‐200a overexpression in CRPC cells markedly suppressed cellular proliferation and facilitated apoptosis. In vivo studies indicated that overexpression of miR‐200a inhibited growth and metastasis of prostate cancer. The luciferase reporter assay demonstrated that BRD4 is a direct target gene of miR‐200a and it could reverse miR‐200a‐mediated biological effects in prostate cancer cells. Most importantly, our findings indicated that miR‐200a suppresses the progression of CRPC by inhibiting the activation of BRD4‐mediated AR signaling. This finding provides the foundation for the development of more personalized therapeutic approaches for CRPC patients. Abstract : In this study, we provide the convincing evidences to the conclusion that miR‐200a suppresses the progression of castration‐resistant prostate cancer by inhibiting the activation of BRD4‐mediated androgen receptor signaling. This finding provides the foundation for the development of more personalized therapeutic approaches for castration‐resistant prostate cancer patients.